Tick size change and market quality in the U.S. treasury market - Michael J. Fleming; Giang H. Nguyen; Francisco Ruela (Federal Reserve Bank of New York, 2019)
This paper studies a recent tick size reduction in the U.S. Treasury securities market and identifies its effects on the market's liquidity and price efficiency. Employing difference-indifference regressions, we find that the bid-ask spread narrows significantly after the change, even for large trades, and that trading volume increases. Market depth declines markedly at the inside tier and across the book, but cumulative depth close to the top of the book changes little or even increases slightly. Furthermore, the smaller tick size enables prices to adjust more easily to information and better reflect true value, resulting in greater price efficiency. Price informativeness remains largely similar before and after, suggesting that the reduction in trading costs does not result in increased information acquisition. However, there is clear evidence of an information shift from the futures market toward the smaller-tick-size cash market. Overall, we conclude that the tick size reduction improves market quality.
Keywords: D14; G01; G12; G18; 330; tick size reduction; bid-ask spread; market liquidity; price efficiency; Treasury securities